Подотчетность и эффективность регуляторной политики: пример банковского сектора - Купряшин, Геннадий; Бодров, Ярослав (Вопросы государственного и муниципального управления, 2014)
This paper examines the contradiction between the accountability and cost effectiveness of regulatory policy at a time when the “delegation” model is dominant. Using the banking sector as a case study, it shows the relationship between formal and informal practices during volatile international and domestic market conditions. The authors analyze the practice of regulation by the Bank of Russia (Bank Rossii), the central bank of the Russian Federation, of a minimum level of capital and risk management at a particular commercial bank. The analysis is based on regulations and consolidated statistical data from the central bank and reporting data from lending institutions. The authors’ principal conclusions show that, given the closed nature of the decisionmaking process, banking-sector actors set up unofficial interaction channels in addition to legal ones, and this intensifi es distrust in the market. Hence the capital ratio standard that is used in the reporting documents of lending institutions is not an accurate indicator of a bank’s financial stability. Given the weak institutions, the tasks of cost effectiveness are better served by a hybrid model of accountability that is based on a balance between delegation and hands-on participation. This model limits the actors’ ability to unilaterally influence the regulator and thereby reduces the systemic risks of the banking sector.